Parton Distribution Functions for Pseudoscalar Mesons in the Confining Effective Chiral Quark Theory - Hutauruk, Parada Tobel Paraduan; Nam, Seung-il (UI Scholars Hub, 2022)
This review paper presents the gluon, sea, and valence quark distributions of the pseudoscalar (PS) mesons. The calculations of the parton structure of PS mesons are performed using the Bethe-Salpeter equation—Nambu-Jona-Lasinio (BSE-NJL) model, which offers a clear description of the dynamical chiral symmetry breaking (D SB) of the low-energy non-perturbative quantum chromodynamics (QCD), with the help of the Schwinger proper-time regularization scheme that simulates the color QCD confinement. Our results for the dynamical quark mass—which emerged from the spontaneous chiral symmetry breaking (S SB)—are generated via the chiral condensate in the chiral limit and beyond. Results for the valence parton distribution functions for the PS meson at the factorization scale are in excellent agreement with experimental data and the gluon distributions for the pion fitted well with the lattice QCD and Jefferson Lab Angular Momentum (JAM) QCD global fit analysis.